Rotational Barrier and Bond Dissociation Energy and Enthalpy: Computational Study of the Substituent Effects in Para-Substituted Anilines and Phenols - Ali Hussain Yateem (Indonesian Journal of Chemistry, 2022)
This report presents the N–H and O–H bond dissociation energies (BDEs) and enthalpies (BDEts) of 27 para-substituted anilines and phenols using Density Functional Theory (DFT) with functional wB97X-D and basis set 6-31G**. The computed BDEs/ BDEts show a strong correlation with the calculated rotational barrier (RB) around phenyl–NH2 and phenyl–OH bonds of the parent neutral molecules. Electron-withdrawing (EW) substituents increased RB and BDEs/BDEts, while electron-donating (ED) substituents caused opposite behavior. Geometric, atomic, molecular, and spectroscopic properties of NH2 and OH groups in neutral anilinic and phenolic molecules exhibited excellent correlations with RB and BDEs/BDEts. The geometry around heteroatoms of the radicals displayed constant geometrical changes for all substituents. Spin density maps confirmed that the unpaired electrons in radicals are delocalized in heteroatoms and phenyl rings for all the para-substituents. Spin delocalization in both types of radicals was further enhanced in the presence of para-ED substituents. The increase in electronic density around heteroatoms of radicals with the strength of ED substituents was found proportional to that in neutral molecules. Therefore, the N–H and O–H BDE/BDEt are mainly governed by the stabilization/destabilization of the neutral molecules and, to a significantly lower extent, the stabilization of radicals in the case of strong ED groups.